Creating Markets in Malawi : The Road to Recovery : Turning Crisis into Economic Opportunity - Country Private Sector Diagnostic - International Finance Corporation (World Bank, Washington, DC, 2022)
Malawi is at a turning point in its political, social, and economic trajectory. Lazarus Chakwera was sworn in as Malawi’s sixth president in June 2020. This marked a historic moment: the first time in Africa that an opposition candidate won a presidential election following initial results being overturned. After widespread unrest prior to the election, Malawians, especially the youth, have been demanding greater accountability, an end to corruption, and tangible progress on eradicating persistent poverty levels that exceed 70 percent of the population. The average gross national income (GNI) of a Malawian is the third lowest in the world, just US$380 as of 2019. The Chakwera administration will need to find a way to unify the country’s fractured political landscape and deliver on development promises. On top of these challenges, the new administration must also navigate the ongoing and evolving economic shocks of the COVID-19 pandemic. Gross domestic product (GDP) growth expectations for 2020 have been lowered from 4.8 percent to 0.8 percent. Recent efforts to build fiscal and institutional resilience have helped but need to be strengthened. The pandemic’s fallout has weakened the country’s macroeconomic foundations, and the overall risk of debt distress is now high. Meanwhile, human capital gains are at risk. Poverty reduction is expected to stagnate, and overall poverty could potentially worsen. The pandemic will likely exacerbate existing inequalities in economic opportunities for women. Women-owned firms, for example, are primarily concentrated in informal agriculture and services, sectors that lack basic social protections to buffer against economic distress. Female farmers, for example, generally have lower access to productive inputs, information, and liquidity than male farmers, so in times of crisis, their farm productivity and food security can be hit harder.